PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT BINA SEJAHTERA BANGUN PERSADA SERANG BANTEN - Jalaludin, Jojo (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
Getting a profit is not easy, the company must maximize all its efforts and efforts. In a marketing study, the efforts made must be oriented towards customer satisfaction. For companies, customer satisfaction means profit, why is that? because satisfaction shows the number of customers who buy the product or service being sold. Strictly speaking, this study aims to reveal the truth of the effect of service on customer satisfaction. In research, to prove the research findings, a method is used, in this study using quantitative methods and regression analysis. The results showed that customer satisfaction will be born or increase if the company provides maximum service. Among the service efforts needed to increase customer satisfaction are providing accurate information, service providers are alert and polite, and face complaints wisely. The regression estimate shows that customer satisfaction will increase by 0.348. This value indicates the opportunity or likelihood of an increase in satisfaction due to increased service. This means that service is a business package that must be presented in order to increase customer happiness in shopping